High-barrier-property aluminum plastic film, preparation method thereof and lithium battery
The high barrier aluminum-plastic film, featuring a magnetron-sputtered silicon nitride or oxide layer and a thermosetting resin flat layer, addresses the challenge of high water vapor permeability in lithium-ion batteries, enhancing durability and barrier performance for automotive applications.
Patent Information
- Application Number
- CN202411779989.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-18
AI Technical Summary
Current aluminum-plastic films used in lithium-ion batteries for automotive applications fail to meet the high water vapor permeability requirements, with a permeability coefficient of 10^-6 g/m²·d·atm, which is beyond the capabilities of existing production methods.
A high barrier aluminum-plastic film is developed, comprising a silicon nitride or oxide layer by magnetron sputtering, a flat layer formed with a thermosetting resin mixture of aminoalkyl ester oligomers and multifunctional thiols, and adhesive layers, enhancing the film's flexibility and durability.
The film achieves improved water vapor and oxygen barrier performance, flexibility, and resistance to wear and tear, effectively extending the lifespan of lithium-ion batteries by preventing gas and moisture ingress.
Smart Images

Figure CN119636190A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-plastic films, and in particular relates to an aluminum-plastic film with high barrier performance, a preparation method thereof, and a lithium battery. Background Art
[0002] With the development of lithium-ion batteries, the demand for high-performance battery packaging materials continues to drive the technical research of soft packaging materials. Aluminum-plastic film is light in weight and thin in thickness, which can achieve higher battery capacity and energy density, and is an important packaging material for soft-pack lithium-ion batteries.
[0003] Since soft-pack lithium-ion batteries contain a variety of organic solvents and lithium salts, such as ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), dimethoxyethane (DME), dimethyl carbonate (DMC), lithium hexafluorophosphate (LiPF6), lithium hexafluoroarsenate (LiASF6) and ethyl methyl carbonate (EMC), these solvents have the characteristics of strong polarity and permeability. At the same time, the lithium salts in the battery are easily hydrolyzed and can quickly produce highly corrosive hydrofluoric acid and other gases when they come into contact with water, causing battery inflation, reduced cycle life and other electrical properties (capacity, insulation, etc.) and even rapid battery failure. Therefore, the requirements for the water vapor barrier performance of the packaging material aluminum-plastic film are very high.
[0004] The water vapor permeability coefficient of traditional aluminum-plastic film is required to reach 10 -4 g / m 2 ·d·1atm, while the service life of a general family car is 10 to 20 years. The aluminum plastic film used for automotive power lithium-ion batteries has higher water vapor barrier performance requirements. Generally, the water vapor permeability coefficient must be at least 10 -6 g / m 2 ·d·1atm, which is difficult to achieve with the current aluminum-plastic film production process.
[0005] Therefore, how to provide an aluminum-plastic film for power lithium-ion batteries that meets the water vapor permeability requirements of automobiles is a technical problem that urgently needs to be solved in this field.
[0006] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0007] The embodiments of the present disclosure at least provide an aluminum-plastic film with high barrier performance, a preparation method thereof, and a lithium battery.
[0008] In the first aspect, an embodiment of the present disclosure provides an aluminum-plastic film with high barrier performance, which includes, from top to bottom: a magnetron sputtering layer, a flat layer, a PET film, a first bonding layer, a nylon film, a second bonding layer, an aluminum foil, a third bonding layer and a CPP film; wherein the magnetron sputtering layer is any one or a combination of two of a silicon nitride layer and a silicon oxide layer; the flat layer is formed by a thermosetting composition, and the thermosetting composition includes a difunctional polyurethane acrylate oligomer and a multifunctional thiol compound.
[0009] In an optional embodiment, the thermal curing composition comprises, by mass, 30-40 parts of a difunctional polyurethane acrylate oligomer, 15-34 parts of a multifunctional thiol compound, 1-5 parts of a thermal initiator, 1-5 parts of a leveling agent and 20-45 parts of a solvent.
[0010] In an optional embodiment, the multifunctional thiol compound includes any one of trimethylolpropane tris(3-mercaptopropionate) and bis(3-mercaptopropionic acid)ethylene glycol or a combination of both.
[0011] In an optional embodiment, the thermal initiator includes any one of azobisbutyl nitrile and dibenzoyl peroxide or a combination of both.
[0012] In an optional embodiment, the thickness of the magnetron sputtering layer is 20-80 nm.
[0013] In an optional embodiment, the thickness of the planar layer is 1-2 μm.
[0014] In an optional embodiment, the PET film has a thickness of 10-15 μm.
[0015] In an optional implementation, the thickness of the first adhesive layer, the second adhesive layer and the third adhesive layer is 3-5 μm; the first adhesive layer, the second adhesive layer and the third adhesive layer are formed of polyurethane glue.
[0016] In the second aspect, the embodiment of the present disclosure also provides a method for preparing an aluminum-plastic film with high barrier performance as described above, comprising the following steps: step S1, coating an acid-resistant liquid on both sides of an aluminum foil to form an acid-resistant film; step S2, configuring a thermosetting composition to form a thermosetting coating liquid, and coating it on one side of a PET film and heating it at a high temperature to obtain a flat layer; step S3, magnetron sputtering on the flat layer to obtain a magnetron sputtering layer; step S4, coating the other side of the PET film with polyurethane glue and then compounding it with nylon, and the compounding temperature is 75-95°C; step S5, coating the matte surface of the aluminum foil with polyurethane glue and then compounding it with nylon, and the compounding temperature is 75-95°C; step S6, coating the bright surface of the aluminum foil with polyurethane glue and then compounding it with the corona-treated surface of the CPP film, and the compounding temperature is 75-95°C to obtain an aluminum-plastic film with high barrier performance.
[0017] In a third aspect, the embodiments of the present disclosure also provide an aluminum-plastic film with high barrier properties as described above.
[0018] The beneficial effects of the present invention are that the high-barrier aluminum-plastic film and its preparation method, and the lithium battery prepare the flat layer by adopting a thermosetting composition, with a difunctional polyurethane acrylate oligomer as the main resin, and the resin has excellent flexibility. The sulfide bond in the multifunctional thiol compound enhances the tensile performance of the flat layer, so as to overcome the disadvantage that the flat layer of the traditional PET film has insufficient tensile performance. The flat layer of the traditional PET is prone to cracks during the aluminum-plastic film shell punching process, and the cracks will seriously affect the barrier effect of the material. The present invention provides a flat layer with excellent flexibility. During the stretching process of the aluminum-plastic film, the flat layer is uniformly stretched. The outer magnetron sputtering layer and the flat layer also enhance the wear resistance and wear resistance of the aluminum-plastic film.
[0019] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0020] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0022] Figure 1 A schematic structural diagram of an aluminum-plastic film with high barrier properties provided in an embodiment of the present disclosure.
[0023] In the figure:
[0024] 1. Magnetron sputtering layer; 2. Flat layer; 3. PET film; 4. First bonding layer; 5. Nylon film; 6. Second bonding layer; 7. Aluminum foil; 8. Third bonding layer; 9. CPP film. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0027] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0028] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0029] The traditional PET flat layer is generally made of high-functionality polyurethane acrylate as the main resin through light curing. The flat layer has poor tensile properties and is prone to cracking or delamination during the stretching process. Once used on aluminum-plastic film, it will reduce the punching performance of the entire structure and will not improve the barrier effect of the structure.
[0030] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0031] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0032] Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0033] An embodiment of the present disclosure provides an aluminum-plastic film with high barrier performance, which includes, from top to bottom: a magnetron sputtering layer, a flat layer, a PET film, a first bonding layer, a nylon film, a second bonding layer, an aluminum foil, a third bonding layer and a CPP film; wherein the magnetron sputtering layer is any one of a silicon nitride layer and a silicon oxide layer or a combination of two; the flat layer is formed by a thermosetting composition, and the thermosetting composition includes a difunctional polyurethane acrylate oligomer and a multifunctional thiol compound.
[0034] In some embodiments, specifically, the thermal curing composition includes, by mass, 30-40 parts of a difunctional polyurethane acrylate oligomer, 15-34 parts of a multifunctional thiol compound, 1-5 parts of a thermal initiator, 1-5 parts of a leveling agent, and 20-45 parts of a solvent.
[0035] In some embodiments, specifically, the difunctional polyurethane acrylate oligomer is preferably polyurethane acrylate model WDS-2250 produced by Shandong Shoucheng Chemical Co., Ltd.
[0036] In some embodiments, specifically, the multifunctional thiol compound includes any one of trimethylolpropane tris(3-mercaptopropionate) and bis(3-mercaptopropionic acid) glycol or a combination of both.
[0037] In some embodiments, specifically, the thermal initiator includes any one of azobisbutyl nitrile and dibenzoyl peroxide or a combination of both.
[0038] In some embodiments, specifically, the leveling agent is used to improve the leveling effect of the thermal curing coating liquid, and BYK-320 with a recoating function is preferred.
[0039] In some embodiments, specifically, the solvent is preferably methyl isobutyl ketone.
[0040] In some embodiments, specifically, the thickness of the magnetron sputtering layer is 20-80 nm.
[0041] In some embodiments, specifically, the thickness of the planar layer is 1-2 μm.
[0042] In some embodiments, specifically, the thickness of the PET film is 10-15 μm.
[0043] In some embodiments, specifically, the thickness of the first bonding layer, the second bonding layer and the third bonding layer is 3-5 μm; the first bonding layer, the second bonding layer and the third bonding layer are formed by polyurethane glue, the polyurethane glue of the first bonding layer is preferably provided by Shanghai Weike Optoelectronic New Materials Co., Ltd., and the product model is VN930, the polyurethane glue of the second bonding layer is preferably provided by Shanghai Weike Optoelectronic New Materials Co., Ltd., and the product model is VN930, and the polyurethane glue of the third bonding layer is preferably provided by Shanghai Weike Optoelectronic New Materials Co., Ltd., and the product model is VP5018.
[0044] The disclosed embodiment also provides a method for preparing an aluminum-plastic film with high barrier performance as described above, comprising the following steps: step S1, coating an acid-resistant liquid on both sides of an aluminum foil to form an acid-resistant film; step S2, preparing a thermosetting composition to form a thermosetting coating liquid, and coating it on one side of a PET film and heating it at a high temperature to obtain a flat layer; step S3, magnetron sputtering on the flat layer to obtain a magnetron sputtering layer; step S4, coating the other side of the PET film with polyurethane glue and then compounding it with nylon, and the compounding temperature is 75-95°C; step S5, coating the matte surface of the aluminum foil with polyurethane glue and then compounding it with nylon, and the compounding temperature is 75-95°C; step S6, coating the bright side of the aluminum foil with polyurethane glue and then compounding it with the corona-treated surface of the CPP film, and the compounding temperature is 75-95°C, to obtain an aluminum-plastic film with high barrier performance.
[0045] The disclosed embodiments also provide an aluminum-plastic film with high barrier properties as described above.
[0046] The performance of the aluminum-plastic film provided by the present invention is tested according to the following method:
[0047] (1) Puncture performance
[0048] Use Shimadzu AGS-X series electronic universal testing machine to test the puncture performance of aluminum-plastic film.
[0049] (2) Wear resistance
[0050] Use Kunshan Jingjia Instrument A20-339 steel wool resistance tester at 50gf / cm 2 Under load, use
[0051] Use #0000 steel wool, weighing 100g, to rub back and forth on the surface of the magnetron sputtering layer 10 times to check whether the magnetron sputtering layer is scratched.
[0052] Criteria:
[0053] If there are 0 scratches, the test result is “Pass”.
[0054] If there is ≥1 scratch, it will be judged as “NG” (failed).
[0055] (3) Punchability
[0056] Punch holes with a shell punching machine. Start punching from 5.0mm, punch 10 samples continuously, check under strong light for no delamination, cracks, or pinholes, then increase by 0.2mm and continue punching for 10 more until it breaks. Record the punching depth before breakage as the limit punching depth.
[0057] (4) Barrier properties
[0058] The water vapor permeability and oxygen permeability were tested using a water and oxygen permeability tester from MOCON at 23°C and 90% RH. The lower the water vapor permeability and oxygen permeability, the higher the water vapor and oxygen barrier rate of the water vapor and oxygen barrier film and the better the water vapor and oxygen barrier property.
[0059] (5) Heat sealability
[0060] Using the Japanese Tester Sangyo TP-701-B heat sealer, two 10cm*10cm aluminum-plastic films were heat-sealed at the heat-sealing layer under the conditions of heat-sealing temperature of 190℃, pressure of 0.5MPa, and heat-sealing time of 3s. After the sample cooled to room temperature, the heat-sealing strength was tested using the Shimadzu AGS-X series electronic universal testing machine.
[0061] Example 1
[0062] The invention provides an aluminum-plastic film.
[0063] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0064] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0065] A heat curing composition was obtained by mixing 40 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 25 parts of a multifunctional thiol compound bis(3-mercaptopropionic acid)ethylene glycol, 3 parts of a thermal initiator azobisbutyl nitrile, 2 parts of a leveling agent BYK-320 and 30 parts of a solvent methyl isobutyl ketone.
[0066] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 1 μm.
[0067] A silicon dioxide layer with a thickness of 40 nm is magnetron sputtered on the hard coating film.
[0068] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at 90°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0069] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 90°C.
[0070] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 90°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0071] After drying, the aluminum foil coated with the second adhesive layer is thermally laminated to the nylon surface of the previous composite structure at a lamination temperature of 90°C.
[0072] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 90°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0073] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 90° C. to obtain a final product.
[0074] Example 2
[0075] Aluminum-plastic film as provided in Example 1.
[0076] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0077] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0078] A heat-curing composition was prepared by mixing 30 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 30 parts of a multifunctional thiol compound trimethylolpropane tris(3-mercaptopropionate), 5 parts of a thermal initiator dibenzoyl peroxide, 5 parts of a leveling agent BYK-320 and 30 parts of a solvent methyl isobutyl ketone.
[0079] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 2 μm.
[0080] A silicon dioxide layer with a thickness of 40 nm is magnetron sputtered on the hard coating film.
[0081] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at 90°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0082] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 75°C.
[0083] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 95°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0084] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 90°C.
[0085] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 100°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0086] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 90° C. to obtain a final product.
[0087] Example 3
[0088] Aluminum-plastic film as provided in Example 1.
[0089] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0090] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0091] A heat curing composition was prepared by mixing 40 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 34 parts of a multifunctional thiol compound bis(3-mercaptopropionic acid)ethylene glycol, 1 part of a thermal initiator dibenzoyl peroxide, 5 parts of a leveling agent BYK-320 and 20 parts of a solvent methyl isobutyl ketone.
[0092] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 1 μm.
[0093] A silicon dioxide layer with a thickness of 40 nm is magnetron sputtered on the hard coating film.
[0094] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at a temperature of 100°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0095] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 80°C.
[0096] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 100°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0097] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 75°C.
[0098] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 75°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0099] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 75° C. to obtain a final product.
[0100] Example 4
[0101] Aluminum-plastic film as provided in Example 1.
[0102] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0103] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0104] A heat curing composition was prepared by mixing 35 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 15 parts of a multifunctional thiol compound bis(3-mercaptopropionic acid)ethylene glycol, 5 parts of a thermal initiator azobisbutyl nitrile, 1 part of a leveling agent BYK-320 and 34 parts of a solvent methyl isobutyl ketone.
[0105] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 1.5 μm.
[0106] A silicon dioxide layer with a thickness of 40 nm is magnetron sputtered on the hard coating film.
[0107] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at 100°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0108] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 95°C.
[0109] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 100°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0110] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 80°C.
[0111] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 100°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0112] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 90° C. to obtain a final product.
[0113] Example 5
[0114] Aluminum-plastic film as provided in Example 1.
[0115] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0116] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0117] A heat curing composition was obtained by mixing 33 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 17 parts of a multifunctional thiol compound trimethylolpropane tris(3-mercaptopropionate), 3 parts of a thermal initiator azobisbutyl nitrile, 2 parts of a leveling agent BYK-320 and 45 parts of a solvent methyl isobutyl ketone.
[0118] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 1 μm.
[0119] A silicon dioxide layer with a thickness of 40 nm is magnetron sputtered on the hard coating film.
[0120] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at a temperature of 100°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0121] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 80°C.
[0122] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 100°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0123] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 95°C.
[0124] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 100°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0125] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 95° C. to obtain a final product.
[0126] Comparative Example 1
[0127] Provided is an aluminum-plastic film.
[0128] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0129] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0130] A heat curing composition was obtained by mixing 30 parts of a difunctional polyurethane acrylate oligomer WDS-2250, 30 parts of a multifunctional thiol compound trimethylolpropane tris(3-mercaptopropionate), 5 parts of a thermal initiator azobisbutyl nitrile, 5 parts of a leveling agent BYK-320 and 30 parts of a solvent methyl isobutyl ketone.
[0131] The above composition was applied to one surface of a 6-micrometer polyethylene terephthalate film, and the formed coating was dried at 100° C. for 4 minutes to obtain a flat layer with a thickness of 1 μm.
[0132] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at a temperature of 100°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0133] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 90°C.
[0134] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 100°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0135] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 90°C.
[0136] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 100°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0137] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 90° C. to obtain a final product.
[0138] Compared with the technical solution provided by the present invention, the aluminum-plastic film provided in Comparative Example 1 is different in that the structure does not contain a magnetron sputtering layer.
[0139] Comparative Example 2
[0140] Provided is an aluminum-plastic film.
[0141] Mix and stir 60 parts of passivation solution AL659 (produced by Yuan'an Technology Co., Ltd.), 20 parts of ethanol and 20 parts of water.
[0142] The diluted passivation solution was coated on both sides of a 40 μm aluminum foil and baked at 250°C for 3 min.
[0143] A silicon dioxide layer with a thickness of 40 nm was magnetron sputtered on one side of the polyethylene terephthalate film.
[0144] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the other side of the above-mentioned polyethylene terephthalate film, and dried at a temperature of 100°C for 1 minute to form a first bonding layer with a thickness of 4um.
[0145] After drying, the adhesive surface of the polyethylene terephthalate film coated with the first adhesive layer is thermally laminated with 12u nylon at a lamination temperature of 90°C.
[0146] The glue of product model VN930 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the matte surface of the treated aluminum foil, and dried at 90°C for 1 minute to form a second adhesive layer with a thickness of 4 um.
[0147] After drying is completed, the aluminum foil coated with the second adhesive layer is thermally laminated with the nylon surface of the composite structure at a lamination temperature of 90°C.
[0148] The glue of product model VP5018 provided by Shanghai Weikai Optoelectronic New Materials Co., Ltd. was prepared according to the recommended ratio, and then coated on the bright surface of the above-mentioned aluminum foil, and dried at a temperature of 100°C for 1 minute to form a third bonding layer. The thickness of the third bonding layer was 4um.
[0149] After drying, the aluminum foil coated with the third adhesive layer is thermally laminated with the 40 um CPP at a lamination temperature of 90° C. to obtain a final product.
[0150] Compared with the technical solution provided by the present invention, the aluminum-plastic film provided in Comparative Example 2 is different in that the structure does not contain a flat layer.
[0151] Table 1 Performance test results of aluminum-plastic films provided by Examples 1-5 and Comparative Examples 1-2
[0152]
[0153] Specifically, the difference of comparative example 1 is that the outer layer of the aluminum-plastic film is not magnetron sputtered, and the magnetron sputtering layer can greatly improve the barrier effect of the material. This structure is similar to the traditional aluminum-plastic film structure and fails to enhance the barrier effect.
[0154] Specifically, the difference of Comparative Example 2 is that the flat layer is not added in the structure, the surface of the PET material is uneven, and magnetron sputtering without treatment does not improve the barrier properties of the material much. In addition, the tensile properties and wear resistance of PET without a flat layer will decrease.
[0155] In summary, the high barrier performance aluminum-plastic film and its preparation method, and the lithium battery prepare the flat layer by adopting a thermosetting composition, with a difunctional polyurethane acrylate oligomer as the main resin. The resin has excellent flexibility, and the sulfide bond in the multifunctional thiol compound enhances the tensile performance of the flat layer, so as to overcome the disadvantage of insufficient tensile performance of the flat layer of the traditional PET film. The flat layer of the traditional PET is prone to cracks during the aluminum-plastic film shell punching process, and the cracks will seriously affect the barrier effect of the material. The present invention provides a flat layer with excellent flexibility. During the stretching process of the aluminum-plastic film, the flat layer is uniformly stretched. The outer magnetron sputtering layer and the flat layer also enhance the wear resistance and wear resistance of the aluminum-plastic film.
[0156] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A high barrier performance aluminum-plastic film, characterized in that: From top to bottom, they include: Magnetron sputtering layer, flat layer, PET film, first bonding layer, nylon film, second bonding layer, aluminum foil, third bonding layer and CPP film; in The magnetron sputtering layer is any one of a silicon nitride layer and a silicon oxide layer or a combination of the two; The planar layer is formed of a thermal curing composition including a difunctional urethane acrylate oligomer and a multifunctional thiol compound.
2. The high barrier performance aluminum-plastic film according to claim 1, characterized in that: The heat curing composition comprises, by weight: 30-40 parts of difunctional polyurethane acrylate oligomer, 15-34 parts of multifunctional thiol compound, 1-5 parts of thermal initiator, 1-5 parts of leveling agent and 20-45 parts of solvent.
3. The high barrier performance aluminum-plastic film according to claim 2, characterized in that: The multifunctional thiol compound includes any one of trimethylolpropane tris(3-mercaptopropionate) and bis(3-mercaptopropionic acid)ethylene glycol or a combination of both.
4. The high barrier performance aluminum-plastic film according to claim 2, characterized in that: The thermal initiator includes any one of azobisbutyl nitrile and dibenzoyl peroxide or a combination of the two.
5. The high barrier performance aluminum-plastic film according to claim 1, characterized in that: The thickness of the magnetron sputtering layer is 20-80 nm.
6. The high barrier performance aluminum-plastic film according to claim 1, characterized in that: The thickness of the flat layer is 1-2 μm.
7. The high barrier performance aluminum-plastic film according to claim 1, characterized in that: The thickness of the PET film is 10-15 μm.
8. The high barrier performance aluminum-plastic film according to claim 1, characterized in that: The thickness of the first bonding layer, the second bonding layer and the third bonding layer is 3-5 μm; The first adhesive layer, the second adhesive layer and the third adhesive layer are formed of polyurethane glue.
9. A method for preparing an aluminum-plastic film with high barrier properties as claimed in any one of claims 1 to 8, characterized in that: The steps include: Step S1, coating the two sides of the aluminum foil with an acid-resistant liquid to form an acid-resistant film; Step S2, preparing a heat-curable composition to form a heat-curable coating liquid, and coating it on one side of the PET film and heating it at a high temperature to obtain a flat layer; Step S3, magnetron sputtering is performed on the flat layer to obtain a magnetron sputtering layer; Step S4, coating the other side of the PET film with polyurethane glue and then laminating it with nylon, the laminating temperature being 75-95° C.; Step S5, coating the matte surface of the aluminum foil with polyurethane glue and then compounding with nylon, the compounding temperature is 75-95° C.; Step S6, after coating the bright surface of the aluminum foil with polyurethane glue, laminating it with the corona-treated surface of the CPP film at a laminating temperature of 75-95° C., to obtain an aluminum-plastic film with high barrier properties.
10. A lithium battery, characterized in that: The high barrier performance aluminum-plastic film as described in any one of claims 1 to 8 is used.
Citation Information
Patent Citations
High water-blocking flame-retardant composite film for lithium battery packaging and preparation method thereof
CN108045026A
Multilayer barrier stack
CN108137832A
Aluminum-plastic composite film and preparation method thereof
CN113878963A
Gas barrier film and production method of the same
JP2014024321A